Virus taxonomy: the database of the International Committee on Taxonomy of Viruses (ICTV). Issue Volume 46:Issue D1(2018) (13th October 2017) - Lefkowitz, Elliot J; Dempsey, Donald M; Hendrickson, Robert Curtis; Orton, Richard J; Siddell, Stuart G; Smith, Donald B
Abstract: The International Committee on Taxonomy of Viruses (ICTV) is charged with the task of developing, refining, and maintaining a universal virus taxonomy. This task encompasses the classification of virus species and higher-level taxa according to the genetic and biological properties of their members; naming virus taxa; maintaining a database detailing the currently approved taxonomy; and providing the database, supporting proposals, and other virus-related information from an open-access, public web site. The ICTV web site (http://ictv.global ) provides access to the current taxonomy database in online and downloadable formats, and maintains a complete history of virus taxa back to the first release in 1971. The ICTV has also published the ICTV Report on Virus Taxonomy starting in 1971. This Report provides a comprehensive description of all virus taxa covering virus structure, genome structure, biology and phylogenetics. The ninth ICTV report, published in 2012, is available as an open-access online publication from the ICTV web site. The current, 10th report (http://ictv.global/report/ ), is being published online, and is replacing the previous hard-copy edition with a completely open access, continuously updated publication. No other database or resource exists that provides such a comprehensive, fully annotated compendium of information on virus taxa and taxonomy.